The meaning of care : the social construction of care for elderly people - Weicht, Bernhard (Palgrave Macmillan, 2020)
Bernhard Weicht provides a multi-layered analysis of how we understand and construct care in everyday life, the meanings it has for ourselves, our families, our relationships, identities and our sense of society and what is right and proper, making an original contribution to the discussion of the nature of care ethics and its political potential